Financial Governance Assistance and Village Potential Optimization Towards an Independent and Prosperous Village in Senganan Village, Tabanan - I Gusti Ngurah SANJAYA; A.A. Ayu Erna Trisna DEWI; Ida Bagus Made Putra MANUABA; I Gusti Ngurah Adi GUNA; Gusti Ayu Putu Rosita DEWI (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2025)
Senganan Village, Tabanan Regency, faces fundamental problems in financial governance and village potential management, which hinder the achievement of community independence and prosperity. This Community Service Program (PKM) aims to increase the capacity of village officials in transparent and accountable financial management, as well as optimize local potential to encourage economic independence. The method used is participatory-educational mentoring, including quarterly monitoring and evaluation, outreach, training, and direct involvement in resolving BUMDes issues and budget planning. There has been an increase in village officials' understanding of financial management, the formation of a BUMDes Rescue Team, and the realization of financial governance socialization attended by all village elements. Program outputs have been published through online and print media. Ongoing mentoring is needed to ensure the sustainability of the program and the achievement of an independent and prosperous village